Amylopectin chain length distribution in grains of japonica rice as affected by nitrogen fertilizer and genotype. (September 2016) - Yang, Xiaoyu; Bi, Junguo; Gilbert, Robert G.; Li, Ganghua; Liu, Zhenghui; Wang, Shaohua; Ding, Yanfeng
Abstract: This study investigated the chain length distribution (CLD) of two japonica rice cultivars under six nitrogen (N) treatments by high performance size exclusion chromatography, with the aims to elucidate the effect of N on rice quality and its biological mechanism. Results showed significant influence of N on CLD. In comparison with low N rate, high N lowered the percentage of short amylopectin branches. Fitting with the CLD model of Wu-Gilbert, it suggested that relative activity of SBE to SS was lower at high N rate, thus producing fewer short amylopectin branches. Comparison of CLD between N rates and between cultivars revealed that decrease in short amylopectin branches or the relative ratio of short to long amylopcetin branches correlated with increase in flour gelatinization temperatures (To, Tp, and Tc ) and decrease in pasting values (except PaT) and amylose-lipid gelatinization temperatures. In addition, quality traits of Wuyujing3, a cultivar with premium eating quality, expressed stably across N treatments compared with the high-yielding cultivar Wuyunjing7. Highlights: We aimed to elucidate N effect on chain length distribution of amylopectin. N lowered the ratio of short chains of amylopectin in rice grain. N decreased the relative activity of SBE to SS. Quality traits of premium rice cultivar expressed stably across N treatments.